(untitled) (Research, Society and Development, 2026)
This article aims to analyze the impacts of orthodontic treatments on children with special needs, considering the clinical, behavioral, and therapeutic specificities involved in this type of care. The methodology used was a literature review, conducted through a survey of scientific articles, manuals, and technical documents published between 2014 and 2025. The search was conducted in databases such as SCIELO, CAPES Periodicals Portal, and Google Scholar, focusing on studies related to conditions such as Down Syndrome and Autism Spectrum Disorder. Publications addressing difficulties in dental care, prevalence of malocclusions, motor and sensory limitations, as well as clinical approach strategies for these patients were selected. The results indicate that children with special needs have a greater predisposition to occlusal alterations and challenges during dental care, due to behavioral, neurological, and functional factors. Despite these difficulties, the studies analyzed demonstrate that orthodontic treatment can bring significant benefits to oral health, improve masticatory function, and contribute to the quality of life of these children. It is concluded that orthodontic treatment is possible and effective when performed in an individualized manner, with clinical adaptations and follow-up by a multidisciplinary team.